Chronological Changes in Anterior Knee Stability after Anatomical Anterior Cruciate Ligament Reconstruction Using Bone–Patellar Tendon–Bone and Hamstring Grafts - Kawaguchi, Kohei; Taketomi, Shuji; Inui, Hiroshi; Yamagami, Ryota; Nakazato, Keiu; Takagi, Kentaro; Kage, Tomofumi; Kawata, Manabu; Tanaka, Sakae (The Journal of Knee Surgery, 2019)
The clinical outcomes of anterior cruciate ligament (ACL) reconstruction are typically evaluated at specific time points only. This study aimed to characterize the chronological changes in anterior knee stability after anatomical ACL reconstruction and to compare the anterior knee stability achieved with bone–patellar tendon–bone (BPTB) and hamstring tendon (HT) grafts. A total of 59 patients underwent anatomical rectangular tunnel ACL reconstruction using the BPTB graft and 23 patients underwent anatomical double-bundle ACL reconstruction using the HT graft. Anterior knee stability was quantitatively assessed using the KneeLax 3 arthrometer at 6 months, 1 year, and 2 years after surgery using side-to-side differences. The values for anterior knee stability using the BPTB graft were 0.3 mm after 6 months, 0.2 mm after 1 year, and 0.2 mm after 2 years, and no significant differences were observed during the postoperative study period. Meanwhile, the values for anterior knee stability using the HT graft were −0.3 mm after 6 months, 0.5 mm after 1 year, and 1.2 mm after 2 years, and anterior knee stability decreased chronologically from 6 months up to 2 years. Regarding anterior stability, the HT graft showed significant laxity compared with the BPTB graft only after 2 years. No chronological changes in anterior stability were observed from 6 months up to 2 years after ACL reconstruction using the BPTB graft, whereas anterior laxity developed during the same period after ACL reconstruction using the HT graft. This is a Level IV, therapeutic case series study.
Keywords: anterior cruciate ligament; anterior stability; chronological change; bone–patellar tendon–bone; hamstring tendon